Cardiothoracic ratio (CTR) measured on post-mortem computed tomography (PMCT) – Pre- and post-ventilation. (March 2016) - James, Pippa; Morgan, Bruno; Rutty, Guy N; Brough, Alison
Abstract: The cardiothoracic ratio (CTR) is commonly used as an indicator of cardiomegaly in clinical radiology. CTR is generally calculated using measurements from chest radiographs. More recently, a number of studies have used computed tomography (CT). This has not been attempted using with post-mortem ventilation, which would more closely mimic the inspiratory breath hold phase chest radiograph used for clinical CTR. The aim of this study was to determine whether CTR can be measured on post-mortem CT (PMCT), whether it correlates with heart weight at autopsy and suggests cardiomegaly, and what effect ventilated PMCT (VPMCT) has on CTR measurements. CTR (%) was measured on PMCT scans pre and postventilation using a method designed to mimic the deep inspiration and breath hold clinical thoracic CT, and compared with heart weights measured at autopsy with cardiomegaly defined from normal heart weight tables scaled for body size and sex. Forty-two cases with both PMCT and VPMCT were consented for research. Results showed excellent measurement repeatability. VPMCT reduced heart diameter and CTR. The best CTR threshold to correlate cardiomegaly was 50% for PMCT (sensitivity and specificity (S&S)=89% and 71%) and 44% for VPMCT (S&S=79% and 71%). The heart diameter thresholds were 130 mm for PMCT (S&S=89% and 93%) and 114 mm for VPMCT (S&S=93% and 86%). Both CTR and heart diameter, using both PMCT and VPMCT, correlated well with heart weight at autopsy. However, using VPMCT and CTR did not give any advantage to measuring heart size on standard PMCT in this study. Highlights: Post-mortem ventilation reduces heart diameter and CTR. A CTR threshold of 50% for PMCT and 44% for VPMCT correlates to cardiomegaly. A heart diameter of 130 mm for PMCT and 114 mm for VPMCT correlates with cardiomegaly. PMCT and VPMCT can both indicate cardiomegaly, by altering thresholds accordingly.